Revitalisasi RRI dan TVRI Menghadapi Pemilu 2014 - Ahmad Budiman (Program Studi Ilmu Komunikasi, 2013)
Regarding to the institutional nature which is now independent and serving public interest, TVRI and RRI are very compatible to be count on in Election 2014. But there are still quite many obstacles for these institutions to handle. Revitalization of TVRI and RRI has to be implemented immediately in the scope of facing Election 2014. Some strategic steps can be taken, include the guarantee that is resulting in more perfect and more comprehensive Bill or regulation, quality control of Election broadcasting programs, the broadcasters’ quality and quantity which are supported by creative human resources quality enhancement, and also in the matter of budget increase for those issues.